2006
DOI: 10.1007/s00534-005-1096-7
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence at hepaticojejunostomy 9 years after resection of bile duct cancer with superficial flat spread

Abstract: We report a male patient aged 45 years, who in 1993 had been diagnosed as having middle bile duct cancer and had received a pancreatoduodenectomy. Histopathology showed a nodular tumor with the main lesion in the middle bile duct and superficial spreading in both proximal and distal directions (which was not observed macroscopically), and residual tumor in the epithelium of the cut edge near the liver. The patient underwent follow-up without postoperative adjuvant therapy. In 2002, 9 years after the operation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Carcinomas with SE showed no portal infiltration and less lymph node metastasis compared to those without SE, which may indicate the potential for lower cases of local recurrence with a long disease-free period by follow-up after initial resection. Growth seems slow in carcinomas with SE and, although care must be taken regarding tumor recurrence for a long period of >10 years (22,23). At this stage, extensive curative resection was necessary for BDCs either with SE or without SE regardless of poorer prognostic influences, as surgical resection was the only hope for long-term survival in BDC patients (2).…”
Section: Discussionmentioning
confidence: 99%
“…Carcinomas with SE showed no portal infiltration and less lymph node metastasis compared to those without SE, which may indicate the potential for lower cases of local recurrence with a long disease-free period by follow-up after initial resection. Growth seems slow in carcinomas with SE and, although care must be taken regarding tumor recurrence for a long period of >10 years (22,23). At this stage, extensive curative resection was necessary for BDCs either with SE or without SE regardless of poorer prognostic influences, as surgical resection was the only hope for long-term survival in BDC patients (2).…”
Section: Discussionmentioning
confidence: 99%
“…Several research groups reported that survival following resection was comparable between patients who had negative ductal margins (median survival time, 33‐55 months) and those who had positive ductal margins with carcinoma in situ (median survival time, 37‐99 months) 26, 27, 28, 31, 32, 35. Although residual carcinoma in situ at the ductal margins does not have a strong adverse effect on survival in patients with extrahepatic cholangiocarcinoma, it may result in late local recurrence 26, 27, 28, 29, 31, 32, 34, 36, 53, 54, 55, 56, 57…”
Section: Biological Behavior Of Residual Carcinoma In Situmentioning
confidence: 99%
“…In addition, we also reported two cases of late recurrence of extrahepatic bile duct carcinoma with intraepithelial spread after surgery. 4,5 However, the clinicopathological characteristics of extrahepatic bile duct carcinoma with intraepithelial spread have been barely reported. It has not been revealed whether or not intraepithelial-spreading bile duct carcinoma has unique pathological characteristics or intraepithelial spread impacts postoperative survival.…”
mentioning
confidence: 99%